Disclosing Public Values: Citizens' Perspectives Based on Group Model Building. Issue 2 (4th March 2022) - Vaandrager, David; Marks, Peter
Abstract: This article presents a tool to disclose public values as emergent properties of needs on a systemic basis applied to a city district in Rotterdam. A tool which enables the public manager to identify public values in any territory based on how people think and feel about society. To accomplish this, it uses Group Model Building (GMB) principles to elicit the mental models that individuals use to make sense of their environment. The results show how the tool enhances a manager's situational awareness and could assists him with information-driven service delivery.